Hybrid AC/DC building distribution network for renewable integration and lift system - part III - Lim, Kai Cong (Nanyang Technological University, 2023)
The purpose of this report is to summarize the research work done for the project, Hybrid AC/DC Building Distribution Network for Renewable Integration and Lift System – Part III (Project Number A1121-221).